Pendekatan Strategis Bakamla untuk Pengawasan Penangkapan Ikan Secara Ilegal di Wilayah Natuna - Rapika Rapika; Ardi Putra; Eki Darmawan (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
Illegal fishing is a form of maritime crime that threatens the sustainability of marine resources and causes significant economic losses for the country, particularly for coastal communities such as those in Natuna Regency. This activity not only harms the fisheries sector but also impacts food security, social stability, and the marine ecosystem. This study aims to examine in depth the surveillance strategy implemented by the Maritime Security Agency (Bakamla) in combating illegal fishing practices in Natuna waters. The research method used is a qualitative descriptive approach with data collection through in-depth interviews and analysis of Bakamla's strategic documents. The theoretical framework used refers to the concept of strategy according to Fred R. David (2016), which includes strategy formulation, implementation, and evaluation. The results of the study indicate that Bakamla has formulated a surveillance strategy by relying on 24-hour sea patrols, utilizing technologies such as the Automatic Identification Sistem (AIS), radio communications, and satellites, and establishing cross-agency collaboration including the Indonesian Navy, the Ministry of Maritime Affairs and Fisheries, and local government officials. The strategy was implemented through rotating patrols, outreach activities for fishermen and coastal communities, and the establishment of a public reporting channel to facilitate the dissemination of information regarding illegal activities. However, the implementation of this strategy still faces obstacles, including limited operational budgets, inadequate patrol fleets, and suboptimal response to public reports. Evaluation of the monitoring strategy showed positive impacts in the form of increased public awareness and participation, as well as a decrease in cases of fish theft in several vulnerable areas. However, the level of public involvement in reporting and independent monitoring still needs to be increased so that the monitoring strategy can be more effective and sustainable in safeguarding the sovereignty of Indonesia's marine resources.